Satanic Mills or Silicon Islands? : The Politics of High-Tech Production in the Philippines - McKay, Steven C. (Cornell paperbacks., 2018)
Satanic Mills or Silicon Islands? challenges the myth of globalization's homogenizing power, arguing that the uniqueness of place is becoming more, not less important. Steven McKay documents how multinational firms secure worker control and consent by reaching beyond the high-tech factory and into local labor markets. He also traces the rise of a new breed of privatized export processing zones, revealing the state's--in these cases, the Philippines--revamped role in the wider politics of global production. Finally, McKay gives voice to the women workers themselves, as they find meaning, identity, and agency on and beyond the "new" shop floor. This book deftly weaves together three critical strands of global studies: Southeast Asia as a key site of global production, the organization of work in advanced electronics, and working-class conditions under globalization. Drawing on the author's rich analysis of four multinational electronics firms--from their boardrooms to boarding houses--Satanic Mills or Silicon Islands? makes a unique contribution to the study of work, labor, and high-tech production.